Motivasi Kerja, Penggunaan Teknologi Informasi, Dan Kinerja Karyawan Pada Perusahaan Farmasi: Studi Kasus Di PT. Soho - Patrisius Hendrawan Karunia Ola Manuk; Tito Siswanto (ITB Ahmad Dahlan Jakarta, 2019)
The purpose of this study was to determine the effect of motivation and use of information technology either partially or simultaneously on the performance of employees at PT. Soho Industri Pharmasi East Jakarta. The values ​​are tested in this research using descriptive analysis with quantitative approach. The results showed no positive effect of work motivation on employee performance. This is evidenced by the value of P (probability) in the calculation Structural Equation Modeling (SEM) 0,065 > 0,05 so it does not qualify where P must be less than 0,05. Information technology has a positive effect on employee performance, as evidenced by the results of a P value of 0,00 < 0,05 so that the results of these studies are eligible. Results of the study show the motivation to work simultaneously together with information technology has a positive effect on employee performance. This is proved by the calculation of SPSS where significant value 0,00 < 0,05. Results are eligible where requested significant value should be < 0,05.